Prevalence, Antibiogram, and Multidrug-Resistant Profile of E. coli O157: H7 in Retail Raw Beef in Addis Ababa, Ethiopia - Haile, Aklilu Feleke; Alonso, Silvia; Berhe, Nega; Atoma, Tizeta Bekele; Boyaka, Prosper N.; Grace, Delia (Frontiers in Veterinary Science, 2022)
Escherichia coli O157:H7 is an emerging foodborne pathogen of public health importance. The current study was undertaken to estimate the prevalence and the antimicrobial resistance of E. coli O157:H7 from retailed raw beef in Addis Ababa, Ethiopia. A total of 384 raw beef samples were collected across the ten sub-cities of Addis Ababa. E. coli O157:H7 was isolated following ISO-16654:2001 standard and isolates were tested for resistance to 13 antimicrobials using the Kirby-Bauer disk diffusion method. The study revealed that of the 384 retail raw beef samples examined 14 (3.64%) were positive for E. coli O157:H7 serotype. The risk of a retail raw beef being contaminated with E. coli O157:H7 were 39 per 1000 butcher shops at 90% confidence interval. Of the 14 E. coli O157:H7 isolates, 12 (85.7%) were found to be resistant to two or more drugs tested. The isolates were susceptible to amikacin (100%), ciprofloxacin (100%), and ceftriaxone (100%) but highly resistance to ampicillin (92.8%), nitrofurantoin (92.8%) and tetracycline (50.0%). The current study showed the presence of E. coli O157:H7 serotype and its multiple antibiotic-resistant profiles in retail raw beef, indicating the possible risk of E. coli O157:H7, particularly to raw or undercooked beef consumers.